Critical discourse analysis of university teacher educators' professionalism in Chilean teacher education policy - Yenny Hinostroza-Paredes (Arizona State University, 2020)
This article uses critical discourse analysis (CDA) to interrogate the discursive construction of Chilean university teacher educators' professionalism in government initial teacher education policy and institutional policy enactment documents. The study examines the network of discourses-new managerialist, quality assurance, performance, functionalist professional development-producing a version of professionalism akin to organizational professionalism. Used as a form of managerial control over teacher educators' professional practices, such professionalism exacerbates performativity while reducing professional agency opportunities and consistent professional/academic development. Ultimately, this study contributes to the necessary questioning of Chilean ITE policy reform and the need to examine its effects on university TEs' professional lives and the professional modeling of their student teachers.